Can I Use AI to Understand My Lab Results? A Professional and Academic Perspective - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Keywords: AI in healthcare, lab results interpretation, digital health, artificial intelligence, medical diagnostics, patient autonomy, clinical laboratory
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Machine Learning